SPAM-K: uma aplicação SDN para a definição de padrões visando a redução de falsos na detecção de SPAMs em serviços de correio eletrônico - Guimarães, Wesley Silvério (2023)
Since the 2010s, computer networks have been transformed by the insertion of the Control Plane defined by the SDN philosophy. With the creation of ONF, network element manufacturers started to use the OpenFlow protocol in their equipment to interface with the control plane. If adoption was massive in infrastructure equipment, with Network Functions Virtualization (NFV) reaching border elements, such as firewalls, the same did not happen with applications. This dissertation aims to develop SPAM-K, an application of the SDN/NFV control layer, to control agents of an MHS system, i.e. electronic mail, to introduce the ability to accurately identify undue messages, such as SPAMs. The research involved analyzing anti-spam filters from different MTAs around the world, considering various factors such as efficiency, security and flexibility. SPAM-K introduces a control plane aimed at standardizing authentication protocol implementations and important settings to ensure the sender is authentic. The results show that SPAM-K can significantly improve the efficiency and security of email servers. It is concluded that this project can meet the needs of users, including companies, governments and individuals, ensuring fast and secure delivery of authentic messages in inboxes, thus avoiding time and financial losses.